The power of cute - May, Simon (Princeton University Press, 2019)
An exploration of cuteness and its immense hold on us, from emojis and fluffy puppies to its more uncanny, subversive expressionsCuteness has taken the planet by storm. Global sensations Hello Kitty and Pokémon, the works of artists Takashi Murakami and Jeff Koons, Heidi the cross-eyed opossum and E.T.-all reflect its gathering power. But what does "cute" mean, as a sensibility and style? Why is it so pervasive? Is it all infantile fluff, or is there something more uncanny and even menacing going on-in a lighthearted way? In The Power of Cute, Simon May provides nuanced and surprising answers.We usually see the cute as merely diminutive, harmless, and helpless. May challenges this prevailing perspective, investigating everything from Mickey Mouse to Kim Jong-il to argue that cuteness is not restricted to such sweet qualities but also beguiles us by transforming or distorting them into something of playfully indeterminate power, gender, age, morality, and even species. May grapples with cuteness's dark and unpindownable side-unnerving, artful, knowing, apprehensive-elements that have fascinated since ancient times through mythical figures, especially hybrids like the hermaphrodite and the sphinx. He argues that cuteness is an addictive antidote to today's pressured expectations of knowing our purpose, being in charge, and appearing predictable, transparent, and sincere. Instead, it frivolously expresses the uncertainty that these norms deny: the ineliminable uncertainty of who we are; of how much we can control and know; of who, in our relations with others, really has power; indeed, of the very value and purpose of power.The Power of Cute delves into a phenomenon that speaks with strange force to our age.